DFT investigation on the electronic, optical and thermoelectric properties of novel half-Heusler compounds ScAuX (X = Si, Ge, Sn, Pb) for energy harvesting technologies - Abraham, Jisha Annie; Sharma, Ramesh; Ahmad, Sajad; Dey, Aditya (European physical journal plus, 2021)
We have made systematic effort to investigate the structural, electronic, optical, and thermoelectric properties of Scandium–Gold-based HH compounds ScAuX (X = Si, Ge, Sn, Pb) using FP-LAPW method in the frame work of DFT and semi-classical Boltzmann equations using the constant relaxation time approximation as instigated in Wien2K code. The energy versus volume curves show that the explored compounds are observed to be stable in cubic non-magnetic phase. Electronic band structures as well as DOS plots predict that all explored compounds are indirect semiconductor in nature with TB-mBJ method, having energy gaps less than 0.5 eV, which gives a prediction for them to use as promising candidates for optoelectronic as well as solar cell devices. We can observe a very good optical response for these compounds because of its narrow band gap, predicting its application in photovoltaic applications. Transport properties results predict that these compounds can be used as good thermoelectric material as they have a high figure of merit value at room temperature and it increases with temperature upto 1200 K. The factor figure of mérit (ZT) takes a maximum value of 0.82, 0.72, 0.69 and 0.80 at T = 1200 K for ScAuX (X = Si, Ge, Sn, Pb). We have used ideal p-type or n-type levels to attain optimum ZT from the computed power factor as a function of carrier concentration and chemical potential, and this will provide experimentalists with guidance to find suitable compositions to synthesize thermoelectric materials with higher performance.